Regulation of murine placentogenesis by the retroviral genes Syncytin-A, Syncytin-B and Peg10 - Henke, Christine; Ruebner, Matthias; Faschingbauer, Florian; Stolt, Claus; Schäfer, Natascha; Lang, Nadine; Beckmann, Matthias; Strissel, Pamela; Strick, Reiner (Differentiation, 2013)
The murine placenta has a trichorial structure with two multinucleated syncytiotrophoblast (SCT) layers representing a barrier between the maternal and fetal blood system. Genes of endogenous retroviruses and retrotransposon-derived paternally expressed genes (Peg), remnants of past infections and integrations in the genome, have essential functions in placentogenesis. Previous studies showed that the envelope genes Syncytin-A and Syncytin-B were essential for cell-cell fusion of the SCT. The goal of this study was to analyze the temporal localization and expression of nine genes throughout placental development from embryonic day (E)8.5 to E18.5 using in situ-hybridization and absolute RNA-quantification. These included a comparison of previously characterized genes from the labyrinth Syncytin-A, Syncytin-B, Gcm1, the junctional zone PL-1, PL-2, Plf, Tpbpa with two further characterized genes Peg10 and Tpbpb. Syncytin-A and Syncytin-B RNA localized to SCT-I and SCT-II, respectively. Peg10 RNA localized to all extraembryonic tissues, specifically to the parietal and sinusoidal TGC of the labyrinth layer, which is in contact with SCT-I and the maternal blood. All three retroviral/retrotransposon-derived genes showed the highest expression at E16.5, but Peg10 with 188,917.1 molecules/ng cDNA was 208-fold and 106.8-fold higher expressed than Syncytin-A and Syncytin-B, respectively. Tpbpb localized to the junctional zone and showed the highest expression at E16.5 along with PL-2, Plf, Tpbpa, but not PL-1, which decreased in expression at E10.5. To investigate a role of Syncytin-A, Syncytin-B and Peg10 in cell-cell fusion, we established a cell culture system with fractionated primary trophoblasts from murine placentae. Culturing trophoblasts for up to 72h partly resembled trophoblast development in vivo according to the nine marker genes. Knockdown of Syncytin-A demonstrated a functional regulation of cell-cell fusion, where knockdown of Peg10 showed no involvement in cell fusion. Due to the expression of Peg10 in TGCs, we propose an essential functional role in the fetal-maternal blood system.
EVALuna2:4934